2021
DOI: 10.1021/acssuschemeng.1c00949
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable, Self-Healable, Freezing-Tolerant, and Transparent Polyacrylic Acid/Nanochitin Composite Hydrogel for Self-Powered Multifunctional Sensors

Abstract: To fulfill the current challenges in the hydrogel applications in wearable sensors including low sensitivity, lack of self-healing ability, and nontransparency, we synthesized a polyacrylic acid/nanochitin composite hydrogel with dual cross-linking networks for highly stretchable, transparent, self-healing, and anti-freezing sensors via an eco-friendly method. Dynamic metal-coordination bonds between Al 3+ and carboxyl groups and the hydrogen bonds contributed to the excellent self-healing efficiency of the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 55 publications
(93 reference statements)
2
69
0
Order By: Relevance
“…[ 54 ] This indicates the matched internal resistance of the device was only 3.3 MΩ, which is tens or hundreds times less than that of common reported TENGs. [ 55–58 ] Similar results have been observed from other H‐TENGs as well, [ 59–64 ] with intriguing applications such as wireless real‐time communication, large capacitors charging, temperature sensing, as well as human motion monitoring. The stronger mechanical adhesion and better reliability between the triboelectric layer and hydrogel resulted in the better charge induction.…”
Section: Advantages Of Hydrogels As Ionic Conductors In Tengssupporting
confidence: 76%
See 2 more Smart Citations
“…[ 54 ] This indicates the matched internal resistance of the device was only 3.3 MΩ, which is tens or hundreds times less than that of common reported TENGs. [ 55–58 ] Similar results have been observed from other H‐TENGs as well, [ 59–64 ] with intriguing applications such as wireless real‐time communication, large capacitors charging, temperature sensing, as well as human motion monitoring. The stronger mechanical adhesion and better reliability between the triboelectric layer and hydrogel resulted in the better charge induction.…”
Section: Advantages Of Hydrogels As Ionic Conductors In Tengssupporting
confidence: 76%
“…As one of the most abundant biopolymers, chitin is the main structural component in living organisms, for instance, carb as seen in Figure 3l. Interestingly, a polyacrylic acid (PAA)/nanochitin hydrogel was synthesized via a facial and green approach by Jing et al [64] The developed chitin-based sensors and TENGs can be used to monitor throat movement during speaking, body joint bending, as well as finger gestures. This provides an alternative raw material presenting a direction that can move away from petroleum-based raw materials.…”
Section: Environmental Friendlinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cross-linked PAA can be employed as a medicinal adhesive due to its excellent bonding strength. PAA has hardness and barrier qualities in film form, making it ideal for packaged food [ 48 , 52 ]. Poly (acrylic acid) varies its characteristics in response to changes in ionic strength and pH; for example, at pH < 4, precipitate occurs in aqueous solutions due to the carboxylate groups’ protonation making the polymer sparsely soluble in water [ 53 ].…”
Section: Synthesis and Structure Characteristicsmentioning
confidence: 99%
“…The excellent self-healing properties of the hydrogel were deemed to be the combined effect of the triple helix crosslinking of gelatin and the dynamic reversible crosslinking network formed by the dynamic hydrogen bond between PAA and Gel molecules. Jing et al [62] reported an ultra-stretchable and self-healing composite hydrogel based on polyacrylic acid/nanochitin (PAA/NCT) by introducing dual crosslinked networks. Due to the presence of dynamically reversible metal coordination bonds and multiple dynamic hydrogen bonds, it gave the hydrogel outstanding self-healing efficiency (97%).…”
Section: Self-healingmentioning
confidence: 99%